Unlawful incomes by Islamic banks in Malaysia: an analysis of juristic methods of purification - Mohd Yunus, Saidatolakma; Kamaruddin, Zuraidah; Haneef, Sayed Sikandar Shah; Embong, Rahimah (Research Institute for Islamic Product and Malay Civilization (INSPIRE) Universiti Sultan Zainal Abidin (UniSZA), 2017)
Islamic banks as a matter of principle should not engage in any risky business activities in the process of which they can procure unlawful incomes. Nevertheless, bank as a corporate entity dealing with people of diverse cultures and International companies is bound not to be able to stay away from transactions which could avoid being tainted with unlawful and objectionable incomes. As to how Islamic banks in Malaysia should treat such an income, Islamic law contains some juristic guidelines on the basis of which, some operational rules could be deduced. Accordingly, this study is an attempt to articulate juristic mechanisms by which Islamic banks in Malaysia can weed out the unlawful incomes from their asset.